Prevalence and Treatment of Substance Misuse in Older Adults: Beyond Early Adulthood - Hu J; Kulkarni N; Maliha P; Grossberg G (Dove Medical Press, 2024)
Jiahao Hu, Neha Kulkarni, Peter Maliha, George Grossberg Department of Psychiatry and Behavioral Neuroscience, Saint Louis University School of Medicine, St Louis, MO, USACorrespondence: Jiahao Hu, Monteleone Hall, 1438 South Grand Blvd, St Louis, MO, 63104, USA, Tel +1 314-617-2777, Fax +1 314-977-4876, Email Jiahao.hu@slucare.ssmhealth.comAbstract: Substance misuse, traditionally seen as a problem of early to mid-adulthood, is becoming increasingly prevalent among the older adult population (ages ≥ 65). Diagnosing and treating substance misuse in this vulnerable population is challenging because of multiple pre-existing medical comorbidities as well as polypharmacy. As such, it remains underdiagnosed and underrepresented in the literature. This review provides an overview of the three most commonly misused substances in older adults: alcohol, cannabis, and prescription drugs. It examines epidemiology, societal trends, and treatment options, highlighting the need for targeted research to address the unique challenges faced by older adults. This review also briefly comments on the prevalence and treatment of other illicit drugs in this population.Keywords: older adult, elderly, alcohol use, cannabis use, prescription drug misuse, prevalence